Konsep Urf dalam Hukum Islam Perspektif Syaikh Yasin Alfadani (Padang) dalam Kitab Alfawaid Aljaniyah - Altsaury, Roychan Abdul Aziz; As'ad, Ali (Pusat Studi Aswaja An-Nahdliyyah UNISNU Jepara, 2023)
AbstractÂ Culture represents a controversial source of Islamic law. However, it's not yet clear what kind of culture can serve as a legal foundation, its criteria, and its legitimacy. Using a literature study approach, the objective of this research is to analyze the concept of 'urf (custom) in Islamic law from the perspective of Sheikh Yasin Alfadani in his book